2022
DOI: 10.1186/s12889-022-14295-2
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy alcohol use and intimate partner violence among men and women living with HIV in Uganda

Abstract: Background Intimate partner violence (IPV) and alcohol use are interrelated public health issues. Heavy and frequent alcohol use increase the risk of IPV, but the relationship between alcohol use and IPV (including recent and lifetime IPV victimization and perpetration) has not been well described among persons living with HIV (PWH) in sub-Saharan Africa. Methods We used baseline data from the Drinker’s Intervention to Prevent Tuberculosis study. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 52 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…Finally, the prevalence of sexual violence ranged from 0.60% (a study conducted with a community sample; Frankland & Brown, 2014) to 50% (a study conducted with a forensic sample of men who were concurrently undergoing treatment for domestic violence; Crane et al, 2014), with a median of 9.70 ( M = 13.41; SD = 14.03). Miller et al’s (2022) study reported a prevalence of injury of 1.08%.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Finally, the prevalence of sexual violence ranged from 0.60% (a study conducted with a community sample; Frankland & Brown, 2014) to 50% (a study conducted with a forensic sample of men who were concurrently undergoing treatment for domestic violence; Crane et al, 2014), with a median of 9.70 ( M = 13.41; SD = 14.03). Miller et al’s (2022) study reported a prevalence of injury of 1.08%.…”
Section: Resultsmentioning
confidence: 94%
“…Regarding the overall prevalence of bidirectional violence in intimate relationships, it ranged from 2% (study conducted with a mixed clinical sample; Miller et al, 2022) to 98.4% (study conducted with a mixed clinical sample of individuals in treatment for substance dependence that aimed to analyze the prevalence of IPV perpetration; Arteaga et al, 2015). The median of the overall prevalence of bidirectional violence was 20.25 ( M = 31.53; SD = 27.87).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations